(4x-5)(5x+4)=0

Simple and best practice solution for (4x-5)(5x+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-5)(5x+4)=0 equation:


Simplifying
(4x + -5)(5x + 4) = 0

Reorder the terms:
(-5 + 4x)(5x + 4) = 0

Reorder the terms:
(-5 + 4x)(4 + 5x) = 0

Multiply (-5 + 4x) * (4 + 5x)
(-5(4 + 5x) + 4x * (4 + 5x)) = 0
((4 * -5 + 5x * -5) + 4x * (4 + 5x)) = 0
((-20 + -25x) + 4x * (4 + 5x)) = 0
(-20 + -25x + (4 * 4x + 5x * 4x)) = 0
(-20 + -25x + (16x + 20x2)) = 0

Combine like terms: -25x + 16x = -9x
(-20 + -9x + 20x2) = 0

Solving
-20 + -9x + 20x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-4 + -5x)(5 + -4x) = 0

Subproblem 1

Set the factor '(-4 + -5x)' equal to zero and attempt to solve: Simplifying -4 + -5x = 0 Solving -4 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -5x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -5x = 0 + 4 -5x = 0 + 4 Combine like terms: 0 + 4 = 4 -5x = 4 Divide each side by '-5'. x = -0.8 Simplifying x = -0.8

Subproblem 2

Set the factor '(5 + -4x)' equal to zero and attempt to solve: Simplifying 5 + -4x = 0 Solving 5 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 0 + -5 -4x = 0 + -5 Combine like terms: 0 + -5 = -5 -4x = -5 Divide each side by '-4'. x = 1.25 Simplifying x = 1.25

Solution

x = {-0.8, 1.25}

See similar equations:

| 13=4q+1 | | 9=1/2*x-y | | b+32=19 | | 7x[x-1.8]=0 | | 2q+18=12-6(q+7) | | 2(6x)+16y=12x+32y | | -62-3u=8 | | -y=5y-2 | | -3w^2+8w+22=0 | | 46=3(r+6)+5(r+4) | | 6(3x+4y)=12x+32y | | -(3-5x)=6x-10 | | 21=a^3+b^3+c^3 | | 4-8n+5n=24-95 | | 5x(e^7x)=12 | | 12x^4-26x^2-10=0 | | ln(1.3690)=6ln(1+r) | | 4h-20=4 | | 3sin(t)=2cos^2(t) | | 2a+2a-1=47 | | 24v+11w+15x+20y-28z=27 | | 8x(6x-4)=10 | | 3(3x-4)=-20 | | 28t-23t=100 | | 67w-40w+(-29w)=38 | | n/4-20==1 | | 51g+20g-61g-6g-3g-1=61 | | (2cosx)(-sinx)=0 | | 54/44 | | 1/9(x-6) | | 0=-1/2a-2/3 | | 3x+6=8x+34 |

Equations solver categories